REPLACING SLASH AND BURN PRACTICES WITH SLASH AND COMPOSTING TO REDUCE CARBON DIOXIDE EMISSIONS FROM DEGRADED PEATLAND - Eni Maftuah; Nur Wakhid (Indonesian Agency for Agricultural Research and Development, 2019)
Slash and burn are commonly practiced in opening new field in tropical peatland. This method, if uncontrolled, may cause peat fires and increase CO2 emissions. Therefore, alternative method of peatland preparation for agriculture is needed. The study aimed to obtain peatland preparation technologies to prevent peat fires and reduce CO2 emissions. The study was conducted at degraded peatland in Kalampangan, Central Kalimantan from June to October 2017. Split plot design with three replications was used. The main plot was the type of land arrangement, i.e. without and with raised beds. The subplot was the type of land preparation, i.e. slash and burn, slash followed by composting the weeds, slash and make the weeds as mulches, and slash followed by composting the weeds and accompanied by plastic mulch. Soil characteristics, fires vulnerability, and CO2 emissions were measured before and after land preparation. Results showed that slash and composting reduced CO2 emission from cultivated peatland. Slash and burn resulted 4.98 t CO2 ha-1 emissions per season, which is four times higher than slash followed by composting that produced 1.20 t CO2 ha-1 per season. Groundwater level, redox potential (Eh), soil pH, and soil water content affected CO2 emissions. Groundwater level and water content negatively correlated with CO2 emissions. The shallow water level and the high water content, the lower is CO2 emissions. The Eh and soil pH positively correlated with CO2 emissions. The high positive value of Eh indicates that the soil was in high oxidative conditions, resulting in high CO2 emissions.